2016
DOI: 10.1073/pnas.1524400113
|View full text |Cite
|
Sign up to set email alerts
|

PGL germ granule assembly protein is a base-specific, single-stranded RNase

Abstract: Cellular RNA-protein (RNP) granules are ubiquitous and have fundamental roles in biology and RNA metabolism, but the molecular basis of their structure, assembly, and function is poorly understood. Using nematode "P-granules" as a paradigm, we focus on the PGL granule scaffold protein to gain molecular insights into RNP granule structure and assembly. We first identify a PGL dimerization domain (DD) and determine its crystal structure. PGL-1 DD has a novel 13 α-helix fold that creates a positively charged chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Indeed, some germline transcripts have been shown to at least transiently reside in P granules (Schisa et al 2001;Sheth et al 2010). Recently, PGL-1 was shown to dimerize and to have guanosinespecific RNase activity (Aoki et al 2016). This raises the possibility that PGL-1 directly influences the transcriptome by cleaving its associated mRNAs, although PGL-1's catalytic activity is not essential for its role in fertility (Aoki et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some germline transcripts have been shown to at least transiently reside in P granules (Schisa et al 2001;Sheth et al 2010). Recently, PGL-1 was shown to dimerize and to have guanosinespecific RNase activity (Aoki et al 2016). This raises the possibility that PGL-1 directly influences the transcriptome by cleaving its associated mRNAs, although PGL-1's catalytic activity is not essential for its role in fertility (Aoki et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PGL-1 was shown to dimerize and to have guanosinespecific RNase activity (Aoki et al 2016). This raises the possibility that PGL-1 directly influences the transcriptome by cleaving its associated mRNAs, although PGL-1's catalytic activity is not essential for its role in fertility (Aoki et al 2016). If PGL-1 does indeed have RNase activity in vivo, then an attractive scenario is that it recognizes mRNAs inappropriate for germline development and cleaves them, while allowing germline-appropriate mRNAs to pass through P granules and be translated in the cytoplasm (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Because PGLs are key assembly proteins for P-granules and can form granules on their own 6, 11, 24, 25 , we reasoned that PGLs use multiple self-interactions to drive granule assembly. We previously identified one dimerization domain (DD) centrally in PGL 27 , but DD missense mutations grossly affected protein stability. We postulated the existence of another PGL multimerization domain that might be more amenable to manipulation and again turned to structural analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Assays for granule assembly in mammalian cells implicated the conserved N-terminal region of PGL as critical 25 , and structural studies identified a central dimerization domain (DD) within that conserved region ( Figure 1B ) 27 . Yet higher-ordered self-assembly demands additional PGL-PGL contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings reveal that C. elegans germ 10 granules are major regulators of the germline transcriptome and prevent germ cells from 11 undergoing somatic development, possibly by preventing the expression of somatic factors in the 12 germline ( Figure 8). The mechanism by which P granules perform these functions remains to be 13 for its role in fertility (Aoki et al 2016). If PGL-1 indeed has RNase activity in vivo, then an 23 attractive scenario is that it recognizes mRNAs inappropriate for germline development and cleaves 24 them, while allowing germline-appropriate mRNAs to pass through P granules and be translated in 25 the cytoplasm (Figure 8).…”
Section: The Germlines From Pgl-1 and Glh-1 Single Mutants Also Exprementioning
confidence: 99%